Nanozymes with phosphatase-like activity - Cao, Yu; Zhu, Shudong (Frontiers in Nanotechnology, 2025)
Nanozymes with phosphatase-like activity are a class of artificial nano-catalysts that mimic the catalytic functions of natural phosphatases. They have attracted widespread attention in the biomedical field in recent years owing to their superior stability, controllability, and low cost. Nanozyme demonstrates unique potential in regulating physiological phosphorus metabolism, intervening in disease-related signaling pathways, detecting disease biomarkers, and treating conditions such as tumors and inflammation. Despite significant progress in nanozyme technology for mimicking natural enzymes in recent years, the research field of phosphatase-mimicking nanozymes remains in a relatively preliminary stage. The types and mechanisms of nanozymes with phosphatase-like activity that have been systematically explored remain quite limited. With the deepening understanding of the role of phosphatases in complex biological processes including disease signal regulation, metabolic disorders, and bone disease pathogenesis, there is an urgent need to develop novel nano-materials that simulate phosphatases with more precise functions to meet the catalytic demands of diverse biological environments. This review focuses on recent research advancements in phosphatase-like nanozymes, with a critical summary of different types of nanomaterials. It aims to provide a theoretical basis and technical reference for the development of phosphatase-mimicking nanozymes with high catalytic activity, excellent biocompatibility, and targeted properties. By analyzing the key challenges and research gaps currently facing the field, we aim to provide new ideas for its continued development and accelerate its practical translation in precision medicine.